2002
DOI: 10.1525/maq.2002.16.2.230
|View full text |Cite
|
Sign up to set email alerts
|

Disparate Views of Community in Primary Health Care: Understanding How Perceptions Influence Success

Abstract: The importance of community in primary health care (PHC) is evident in the role of community participation and in the types of programs that are routinely implemented (community health-worker [CHW] programs, community clinics, community-based disease-control programs). Few health care providers and program administrators, however, have considered the meaning of community. Instead, they frequently impose their own definition of community and assume that it corresponds to local realities. This is problematic bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…Yet, an organizational expertise in clinical care did not necessarily translate to optimal outreach [28,29]. The reluctance of one county hospital to adopt new outreach plans to increase access to mammography among uninsured women may have reflected downstream financial concerns with uninsured patients who may rely on the hospital for services other than for reimbursable breast cancer screening services [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, an organizational expertise in clinical care did not necessarily translate to optimal outreach [28,29]. The reluctance of one county hospital to adopt new outreach plans to increase access to mammography among uninsured women may have reflected downstream financial concerns with uninsured patients who may rely on the hospital for services other than for reimbursable breast cancer screening services [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…As Wayland and Crowder's (2002) study demonstrated about the lack of sufficient community health workers in urban Bolivia, the pharmacy may be worth exploring as a venue to reach groups who, like vendors may not spend much time in their home neighborhoods or communities.…”
Section: Discussionmentioning
confidence: 99%
“…Wayland and Crowder (2002) looked at an urban community located in the Andes in Bolivia and the attitudes people in the community had towards community health workers. The growth of the city prevented health workers from being able to make as many visits to communities as normally done.…”
Section: Pharmacies Pharmaceuticals and Friendshipsmentioning
confidence: 99%
“…However, community-based approaches to treatment and surveillance have attracted their own criticisms. Anthropologists Coral Wayland and Jerome Crowder (Wayland & Crowder, 2002) argued that WHO's current definition of community 'ultimately homogenizes what may be heterogeneous groups' by assuming that an aggregate of individuals in a given location will automatically share a 'form of social organization and cohesion…as well as interests and aspirations, including health ' (pp. 232-233).…”
Section: Surveillance and Supervisionmentioning
confidence: 99%